Outcomes From Healthy Eating and Physical Activity Recognition Programs in Early Child Care and Education: A Scoping Review. Issue 1 (January 2023) - Arlinghaus, Katherine R.; Schroeder, Mary; Gold, Abby; Goodman, Lenora P.; Wagner, Gerit; Pass, Molly; Hunt, Shanda; Stang, Jamie
Objective: Recognition programs are designed to incentivize early care and education (ECE) settings to implement childhood obesity prevention standards, yet little is known regarding their efficacy. This scoping review details characteristics, methodologies, and criteria used to evaluate recognition programs, identifies gaps in evaluation, and synthesizes existing evidence. Data Source: A public health librarian created the search strategies for six databases: Ovid MEDLINE, AGRICOLA, CAB Abstracts, PAIS Index, ERIC, and Scopus. Study Inclusion and Exclusion Criteria: Inclusion criteria include recognition program, ECE setting, nutrition or physical activity, and qualitative or quantitative outcomes. Exclusion criteria include programming without recognition component, no ECE setting, no nutrition or physical activity outcome, case studies, or not written in English. Data Extraction: Three researchers independently extracted and complied data into an Excel spreadsheet. Data Synthesis: Tables were created describing location, recognition program criteria, award incentive, study design, study sample, risk of bias, and outcomes (e.g., menu nutrition) evaluated in each study. Results: Three unique recognition programs (described in 7 studies) provided technical assistance, incentives, and training. While outcome measures and study designs varied across programs, it is clear that recognition programs are well accepted and feasible, and one study demonstrated beneficial weight outcomes. Conclusion: Although additional evaluation is needed, recognition programs may be a promising strategy to improve obesity prevention practices in ECE.